ANALISIS TINGKAT KEPUASAN PELANGGAN TERHADAP KINERJA - Arisandi, Devy; Thaha, Atifah; Chusnah, Chusnah (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2019)
Increasing public awareness about the health of the strong competition in the business world, especially the health of their field laboratorium.Never measurement of customer satisfaction, this is the basic of this research is finding a match between the interest rate the elements of service according to the customer with the work done by the company. The study was conducted in the Clinical Laboratory Westerindo Jakarta with 340 respondents. Data collected through questionnaires covered. Analyses were performed using methods Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA). The result of CSI is 0723, where the value is in the category